After Radical Prostatectomy: Erectile Dysfunction Diagnosis and Its Treatment - A Literature Review - Pakos, Kinga; Górczyński, Krzysztof; Majewski, Kornel; Majewska, Aleksandra; Czujkowska, Maria; Kowalewski, Jan; Pyc, Grzegorz; Durmała, Kamila; Bałoniak, Zuzanna; Mączka, Jakub (Quality in Sport, 2024)
Introduction and purpose of work: In the last 10 years, prostate cancer has become the most common cancer in the Polish population of men with the high growth dynamics. Despite the fact that we are getting better with mortality and new surgery techniques, complications in the form of urinary incontinence and erectile dysfunctions after radical prostatectomy are a common problem. This study deals with the second problem, often underestimated by the society, but equally important in maintaining high -quality life. Our goal is to present aethiology, diagnostics and treating patients with erectile dysfunction after radical prostatectomy due to prostate cancer. It can help doctors who usually do not have contact with such patients, understand the problem and manage effective treatment in their daily practice. Method: We searched for studies and articles via PubMed using the keywords prostate cancer, radical prostatectomy, erectile dysfunction. From screened documents identified from literature search, 52 articles were included in our review. Summary: Erection dysfunction is a complex problem, in which the basis is the interaction of the vascular and nervous systems. To diagnose the patient, you need to conduct a thorough interview, generally about medical history and chronic diseases, but also about sex life. After the diagnosis, there are many treatment options to choose from, pharmacological and non-pharmacological. An important aspect of treatment that you cannot forget is psychological support which should start from the moment of diagnosis of prostate cancer. Each method has pros and cons, but effective cooperation with the patient will give the desired results.